Formulation and Optimization of Furosemide Snedds With Variation Concentration of Tween 80 and PEG 400 - Sesilia Putri Nandita; Ilham Kuncahyo; Reslely Harjanti (Journal of Fundamental and Applied Pharmaceutical Science, 2021)
Furosemide is a potent diuretic drug that has low bioavailability. Furosemide can be formulated into nanoemulsion preparations using the SNEDDS method to increase its bioavailability as SNEDDS can form stable nanoemulsions with droplet sizes is less than 200 nm. This study aims to identify the optimum formula for variations in the concentration of surfactant Tween 80 and cosurfactant PEG 400 based on the characterization tests of emulsification time, percent transmittance, and drug loading. The independent variables used in this study were Tween 80 and PEG 400. Seven furosemide SNEDDS formulas from the Simplex Lattice Design (SLD) method were tested for characterization in the form of emulsification time, percent transmittance, and drug loading. The characterization results were optimized using Simplex Lattice Design. The optimum formula was re-characterized, including emulsification time, percent transmittance, drug loading, particle size, zeta potential, and in vitro dissolution. The results were then compared with theoretical values and analyzed using the One-Sample T-test method. Optimization results showed Tween of 61.4922% and PEG 400 of 18.5078% with the characterization of emulsification time 15.25 seconds, percentage transmittance 94.20%, drug loading 50 100.2 ppm, particle size 12.18 nm. Furthermore, the zeta potential was -17.6 mV, and the in vitro dissolution rate reached 106.71% within 15 minutes.